Badania wpływu obciążeń cyklicznych na ściśliwość gytii = Research on the effect of cyclic loading on gyttja compressibility - Wojnicka-Janowska, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The artide presents the results of the research on the compressibility of calcareous gyttia from the region of Międzyrzecz that was subjected to cyclic loading in oedometer. The research made it possible to determine correlations that exist among strains, the compressibility module value and the number of loading cycles.
Keywords: ściśliwość; obciążenia cykliczne; gytia wapienna; compressibility; cyclic loading; gyttja